Manajemen Resiko Pemberian Kredit Kredit Usaha Rakyat(KUR) Pada Perbankan - Difinubun, Muhamad Fagi (Jurnal Online Manajemen ELPEI, 2024)
Kredit Usaha Rakyat (Kur) is a business capital facility from the Bank to productive and viable business actors who need financial assistance but do not yet have additional collateral or sufficient collateral. Lending has the potential for a large risk of loss in the banking world. So in need of proper management and supervision. For this reason, risk management is needed in the process of lending that is distributed. Data collection techniques in this paper using observation, interview, triangulation, and collect data, while for data analysis techniques in this case using the Miles and Huberman model. The results of this writing prove that the implementation of business risk management can minimize the occurrence of payment arrears by debtors.